Mean-Squared Analysis of the Partial-Update NLMS Algorithm10.14209/jcis.2003.9 - Werner, Stefan; L. R. de Campos, Marcello; S. R. Diniz, Paulo (Journal of Communication and Information Systems, 2015)
In this paper, we present mean-squared convergence analysis for the partial-update normalized least-mean square (PU-NLMS) algorithm with closed-form expressions for the case of white input signals. The analysis uses order statistics and the formulas presented here are more accurate than the ones found in the literature for the PU-NLMS algorithm. Simulation results show excellent agreement with the the results predicted by the analysis.